Efficacy of single voxel 1H MR spectroscopic imaging at 3 T for the differentiation of benign and malign breast lesions - KAYA, HANDAN; UĞURLU, MUSTAFA ÜMİT (ELSEVIER SCIENCE INC, 2016)
Purpose: The aim of our study was to evaluate the effect of 1H Magnetic Resonance Spectroscopy (MRS) in differentiating breast lesions. Materials and methods: Single voxel 1H Magnetic Resonance Spectroscopy (1H-MRS) was performed with 3 T magnet in 45 women. The choline cut off point was set semi-quantitavely. Sensitivity, specificity and accuracy of MRS were calculated. Results: Twenty-four of 25 (96%) malignant and 9 of 26 (35%) benign lesions had choline peak. With the use cutoff value of 19,5 MRS provided a 96% sensitivity, 65% specificity and 80% accuracy. Conclusion: MRS has a high diagnostic accuracy in differentiating breast lesions. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: MR spectroscopy; Choline peak; Breast lesions; Biopsy; IN-VIVO; NEOADJUVANT CHEMOTHERAPY; RESONANCE SPECTROSCOPY; CHOLINE CONCENTRATION; CANCER; METABOLITES; EXPERIENCE; MARKER; TUMORS